Guapiaçu virus, a new insect-specific flavivirus isolated from two species of Aedes mosquitoes from Brazil - Geovani de Oliveira Ribeiro (Nature Portfolio, 2021)
Abstract Classical insect-flaviviruses (cISFVs) and dual host-related insect-specific flavivirus (dISFV) are within the major group of insect-specific flavivirus. Remarkably dISFV are evolutionarily related to some of the pathogenic flavivirus, such as Zika and dengue viruses. The Evolutionary relatedness of dISFV to flavivirus allowed us to investigate the evolutionary principle of host adaptation. Additionally, dISFV can be used for the development of flavivirus vaccines and to explore underlying principles of mammalian pathogenicity. Here we describe the genetic characterization of a novel putative dISFV, termed Guapiaçu virus (GUAPV). Distinct strains of GUAPV were isolated from pools of Aedes terrens and Aedes scapularis mosquitoes. Additionally, we also detected viral GUAPV RNA in a plasma sample of an individual febrile from the Amazon region (North of Brazil). Although GUAPV did not replicate in tested mammalian cells, 3′UTR secondary structures duplication and codon usage index were similar to pathogenic flavivirus.